Ferrous Ion Alleviates Lipid Deposition and Inflammatory Responses Caused by a High Cottonseed Meal Diet by Modulating Hepatic Iron Transport Homeostasis and Controlling Ferroptosis in Juvenile Ctenopharyngodon idellus - Hengchen Liu; Shiyou Chen; Yan Lin; Wenqiang Jiang; Yongfeng Zhao; Siyue Lu; Linghong Miao; Xianping Ge (MDPI AG, 2023)
To investigate the mechanisms through which ferrous ion (Fe2+) addition improves the utilization of a cottonseed meal (CSM) diet, two experimental diets with equal nitrogen and energy content (low-cottonseed meal (LCM) and high-cottonseed meal (HCM) diets, respectively) containing 16.31% and 38.46% CSM were prepared. Additionally, the HCM diet was supplemented with graded levels of FeSO4·7H2O to establish two different Fe2+ supplementation groups (HCM + 0.2%Fe2+ and HCM + 0.4%Fe2+). Juvenile Ctenopharyngodon idellus (grass carps) (5.0 ± 0.5 g) were fed one of these four diets (HCM, LCM, HCM + 0.2%Fe2+ and HCM + 0.4%Fe2+ diets) for eight weeks. Our findings revealed that the HCM diet significantly increased lipid peroxide (LPO) concentration and the expression of lipogenic genes, e.g., sterol regulatory element binding transcription factor 1 (srebp1) and stearoyl-CoA desaturase (scd), leading to excessive lipid droplet deposition in the liver (p < 0.05). However, these effects were significantly reduced in the HCM + 0.2%Fe2+ and HCM + 0.4%Fe2+ groups (p < 0.05). Plasma high-density lipoprotein (HDL) concentration was also significantly lower in the HCM and HCM + 0.2%Fe2+ groups compared to the LCM group (p < 0.05), whereas low-density lipoprotein (LDL) concentration was significantly higher in the HCM + 0.2%Fe2+ and HCM + 0.4%Fe2+ groups than in the LCM group (p < 0.05). Furthermore, the plasma levels of liver functional indices, including alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and glucose (GLU), were significantly lower in the HCM + 0.4%Fe2+ group (p < 0.05). Regarding the expression of genes related to iron transport regulation, transferrin 2 (tfr2) expression in the HCM group and Fe2+ supplementation groups were significantly suppressed compared to the LCM group (p < 0.05). The addition of 0.4% Fe2+ in the HCM diet activated hepcidin expression and suppressed ferroportin-1 (fpn1) expression (p < 0.05). Compared to the LCM group, the expression of genes associated with ferroptosis and inflammation, including acyl-CoA synthetase long-chain family member 4b (acsl4b), lysophosphatidylcholine acyltransferase 3 (lpcat3), cyclooxygenase (cox), interleukin 1β (il-1β), and nuclear factor kappa b (nfκb), were significantly increased in the HCM group (p < 0.05), whereas Fe2+ supplementation in the HCM diet significantly inhibited their expression (p < 0.05) and significantly suppressed lipoxygenase (lox) expression (p < 0.05). Compared with the HCM group without Fe2+ supplementation, Fe2+ supplementation in the HCM diet significantly upregulated the expression of genes associated with ferroptosis, such as heat shock protein beta-associated protein1 (hspbap1), glutamate cysteine ligase (gcl), and glutathione peroxidase 4a (gpx4a) (p < 0.05), and significantly decreased the expression of the inflammation-related genes interleukin 15/10 (il-15/il-10) (p < 0.05). In conclusion, FeSO4·7H2O supplementation in the HCM diet maintained iron transport and homeostasis in the liver of juvenile grass carps, thus reducing the occurrence of ferroptosis and alleviating hepatic lipid deposition and inflammatory responses caused by high dietary CSM contents.